The evaluation of nocturia in patients with lower urinary tract symptoms suggestive of benign prostatic hyperplasia and the analysis of the curative effect after medical or placebo therapy for nocturia: a randomized placebo-controlled study - Zhigang Xue; Yunhua Lin; Yongguang Jiang; Nengbao Wei; Jinwen Bi (BMC Urology, 2018)
Abstract Background To study nocturia in patients with lower urinary tract symptoms (LUTS) suggestive of benign prostatic hyperplasia (BPH) after medical or placebo treatment. Methods Patients with LUTS suggestive of BPH from several community clinics were included. Patients completed the International Prostate Symptom Score (I-PSS) questionnaire and a 3-day voiding diary. Urinalysis, prostate-specific antigen (PSA) measurement, and prostate ultrasonography were performed. Nocturnal polyuria (NP) was defined as a nocturnal urine fraction exceeding one third of the daily urine output in elderly men. A total of 148 outpatients were randomized to drug treatment (tamsulosin) or placebo treatment. After 8 weeks of treatment, they were re-evaluated using a 3-day voiding diary, PSA measurement, prostate volume (PV), I-PSS, etc. Results The average I-PSS score was 20.3, storage symptom score was 11.7, voiding symptom score was 8.6, quality of life (QoL) score was 3.7, PV was 40.4 ± 19.4 ml, and nocturnal urine volume (NUV) was 845.7 ± 339.0 ml. The mean frequency of nocturia was 2.3 ± 1.1 per day, and 94% of the patients had a nocturia frequency of more than two times per day. Of these patients, 76.5% had NP. A significant correlation was found between NUV and the amount of water intake at night and 4 h before sleep (r = 0.419,P = 0.002; r = 0.302,P = 0.031). Eighty patients were randomized to drug treatment (tamsulosin) and 68 patients were randomized to placebo treatment. The I-PSS score was 16.8 ± 4.9 to 19.3 ± 5.0 (p = 0.002), the storage symptom score was 10.3 ± 3.4 to 10.7 ± 3.4 (p = 0.007), and the voiding symptom score was 7.5 ± 2.4 to 8.6 ± 2.3 (p = 0.003). The frequency of daytime urination was 7.5 ± 2.6 to 8.1 ± 2.6 (p = 0.002), maximum urine volume (ml) was 372.8 ± 103.3 to 302.8 ± 119.3 (p = 0.007), and morning urine volume (ml) was 280.5 ± 111.7 to 259.5 ± 100.7 (p = 0.003). However, the frequency of nocturia score was 2.8 ± 0.7 to 3.0 ± 0.6 (p = 0.306) and the nocturnal urine volume (ml) was 800.7 ± 323.0 to 845.7 ± 303.5 (p = 0.056), which did not change significantly. There were significant differences between the NP and non-NP groups in the duration of LUTS, first voided urine volume, daytime urination frequency, and the amount of water intake at night and 4 h before sleep. Conclusions Among the symptoms of LUTS, the improvement rates for nocturia were the lowest after medical treatment for BPH. The α-blockers did not improve nocturia, which was a common symptom accompanying LUTS suggestive of BPH. Our results showed that the prevalence of NP was 76.5% and that NP was significantly related to the amount of water intake during the evening and before sleep. Trial registration ISRCTN registry, Trial registration number (TRN): ISRCTN85509614, Date of registration: 30/10/2018. This trial was registered retrospectively.